2007
DOI: 10.1177/0267658307080330
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of tense—aspect in child second language English

Abstract: and to test Gavruseva's aspectual features account, according to which inherent aspectual properties of the verbs such as telicity and punctuality determine which verbs will be non-finite and which verbs will not (Gavruseva, 2002;2003;2004) in child L2 acquisition. Based on longitudinal data from a Turkish child second language (L2) learner of English, we present counter evidence for both hypotheses. First, it is shown that despite the fact that the early production of past tense morphology occurs exclusively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…Many of these studies, however, have shown no clear agreement as to which theoretical explanations should be given to the predictable patterns of acquisition of tense and aspect. Hence, reasons such as the distribution of input (Ayoun and Salaberry 2008;Rhode 1996;Robison 1995;Andersen and Shirai 1994) to which learners are exposed, the influence of the teaching environment (Bardovi-Harlig 1992), L1 influence (Collins 2002(Collins , 2004Sugaya and Shirai 2007) or alternative universal mechanisms (Slabakova 1999;Gavruseva 2002;and Haznedar 2007 for a counterargument) among others, have been advanced in order to provide an explanation for certain robust patterns of the acquisition of tense and aspect morphology. Within the framework of the AH, the goal of this paper is to provide further evidence from cross-sectional data with regard to the acquisition of progressive aspect by learners of English who are bilingual Catalan-Spanish, a language constellation that has not previously been studied in this domain.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies, however, have shown no clear agreement as to which theoretical explanations should be given to the predictable patterns of acquisition of tense and aspect. Hence, reasons such as the distribution of input (Ayoun and Salaberry 2008;Rhode 1996;Robison 1995;Andersen and Shirai 1994) to which learners are exposed, the influence of the teaching environment (Bardovi-Harlig 1992), L1 influence (Collins 2002(Collins , 2004Sugaya and Shirai 2007) or alternative universal mechanisms (Slabakova 1999;Gavruseva 2002;and Haznedar 2007 for a counterargument) among others, have been advanced in order to provide an explanation for certain robust patterns of the acquisition of tense and aspect morphology. Within the framework of the AH, the goal of this paper is to provide further evidence from cross-sectional data with regard to the acquisition of progressive aspect by learners of English who are bilingual Catalan-Spanish, a language constellation that has not previously been studied in this domain.…”
Section: Introductionmentioning
confidence: 99%
“…L1 influence and L1-L2 commonality have challenged the exactitude of the AH, since it appears that some learners have an easier time adjusting to the temporal system of the L2 if their native language has similar aspectual inflections (Collins, 2002;Izquierdo & Collins, 2008). Moreover, certain semantic features of lexical aspect -punctuality, followed by telicity -may be more salient to certain learners (Haznedar, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in Haznedar's (2007) longitudinal study of a child with L1 Turkish at initial stages of L2 English acquisition, her subject initially produced past tense markings on [+punctual] achievement verbs and predicates. Conversely, this subject seldom marked [-punctual] verbs and predicates for aspect at this stage, leaving them in infinitive forms without inflection.…”
Section: The Role Of Lexical Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…She is study hard). It is commonly attested in the early stage of L2 English by learners from diverse L1s, such as Arabic (Mourssi, 2013), Bantu languages (Suzman, 1999), Chinese (Yang, 2014), Hmong (Huebner, 1983), Japanese (Shibata, 2006), Korean (Ahn, 2003(Ahn, , 2006Kim, 2011), Russian (Ionin & Wexler, 2002), Spanish (Fleta, 2003;Mayo et al, 2005), and Turkish (Haznedar, 2007). Not only are the L1s of the learners producing be-insertion diverse, but the phenomenon is highly frequent.…”
Section: Introductionmentioning
confidence: 99%